Kesiapan Pemerintah Daerah dalam Mewujudkan Kota Cerdas di Bandung dan Surabaya - Adi Suhendra (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2017)
This study is about the Smart City. This research is motivated by the emergence of some local governments that make the district a smart city. The purpose of this research is to describe the various efforts made by the local government in realizing the Smart City. This study uses a qualitative method. The results are in get in this study is the concept of intelligent city of Bandung was named the “Smart City Bandung 1.0”. At least there are four basic frame before building a smart city of Bandung namely the Public Service, Administrative Performance Improvement, Building Civic Interaction with the Local Government Data Access and openness to the public. The concept of intelligent city of Surabaya on the theme “e-Government that is composed of” Management of Regional Development “and the system to” Public Service”. There are many efforts undertaken by the city government, both in Bandung and Surabaya. In addition to receiving many awards, during these two loci have been widely used as a role model for other cities in Indonesia. Nevertheless, respectively the creation of intelligent cities is still more the use of a means of information and technology.